Pemberdayaan masyarakat Pemberdayaan masyarakat melalui Program kampung iklim di Desa sukamaju - Yamani, Lucky; Nurlaila; Lilis Karwati (Universitas Negeri Surabaya, 2025)
Economic problems have occurred in society, namely the problem of climate change in the earth's temperature, causing the community's economic activities to be disrupted and threatened, so pro-climate is needed to overcome climate change. This research aims to determine the process of community empowerment through the climate village program in Sukamaju Village. The methods used are qualitative methods, interview techniques, observation and documentation. The results of this research show that community empowerment through the climate village program in Sukamaju Village has an effect on the community's economic level and climate change conditions through the stages: Enabling, Strengthening, Protection, Support and Maintenance. Which means that the empowerment activities of the Climate Village Program, the use of yard land and waste management, have an impact on family income levels through planting food crops, while the income generated from waste management activities is through selling inorganic waste to waste bank partners. Conclusion of community empowerment through the climate village program in Sukamaju Village. So that the community can adapt and prevent climate change and can be a community empowerment concept that is adaptive and mitigating against climate change.